Aging (IntechOpen, 2021)
This edited book, “Aging - Life Span and Life Expectancy”, is a collection of reviewed and relevant research chapters offering a comprehensive overview of recent developments in this field. The book comprises chapters authored by various researchers and edited by an expert active in the research area. All chapters are individually complete but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors and opening new possible research paths for further novel developments.